Critical analysis of the allocation policy for liver transplantation in Brazil - Sette Jr., Hoel; Bacchella, Telesforo; Machado, Marcel Cerqueira César (Revista do Hospital das Clínicas, 2003)
Liver transplantation is now the standard treatment for end-stage liver disease. Given the shortage of liver donors and the progressively higher number of patients waiting for transplantation, improvements in patient selection and optimization of timing for transplantation are needed. Several solutions have been suggested, including increasing the donor pool; a fair policy for allocation, not permitting variables such as age, gender, and race, or third-party payer status to play any role; and knowledge of the natural history of each liver disease for which transplantation is offered. To observe ethical rules and distributive justice (guarantee to every citizen the same opportunity to get an organ), the "sickest first" policy must be used. Studies have demonstrated that death has no relationship with waiting time, but rather with the severity of liver disease at the time of inclusion. Thus, waiting time is no longer part of the United Network for Organ Sharing distribution criteria. Waiting time only differentiates between equally severely diseased patients. The authors have analyzed the waiting list mortality and 1-year survival for patients of the State of São Paulo, from July 1997 through January 2001. Only the chronological criterion was used. According to "Secretaria de Estado da Saúde de São Paulo" data, among all waiting list deaths, 82.2% occurred within the first year, and 37.6% within the first 3 months following inclusion. The allocation of livers based on waiting time is neither fair nor ethical, impairs distributive justice and human rights, and does not occur in any other part of the world.